UTILIZING THE FLIPPED LEARNING TO PROMOTE EFL STUDENT’S ENGAGEMENT; A PRELIMINARY STUDY - Silvina Yuza; Fazri Nur Yusuf (Universitas Widyatama, 2023)
Flipped learning (FL) has been a popular approach for it’s potential in promoting student’s engagement in EFL context particularly. Although it is considered applicable in higher and K-12 education, researches in the latter category are still scarce, especially that reported its implementation in detail. This preliminary action research is involving 14 secondary school students. It focuses on how utilizing FL engage EFL student in learning and what challenges teacher faces during the implementation. Findings indicate that FL implementation combined with teacher’s approach has not yet promoted student’s engagement in learning English. During in-class session, even though the students participated in playing board game in a speaking activity, only few of them kept practicing enthusiastically. Student’s commitment for outclass activities as instructed by the teacher and task completion were still low. The problems identified were that students got less frequent mobile device use after school and their minimum parent’s support. Further action plans are recommended for the follow-up research.